ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN PADA ASURANSI “P” DI KOTA SEMARANG - Nanda Putri Prameswari; Sri Rahayu Tri Astuti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
This study is aimed to (1) knowing how to customer value can influence consumer loyalty at “P” insurance’s consumers, (2) knowing how the appeal of advertising can influence consumer loyalty at “P” insurance’s consumer, and (3) knowing how salesperson’s competencies can influence consumer loyalty at “P” Insurance. The results are (1) Customer value can increase consumer loyalty, (2) The appeal of advertising can increase consumer loyalty, and (3) The competence of salesperson can increase consumer loyalty.